Female, Jewish, and educated : the lives of Central European university women - Freidenreich, Harriet Pass, 1947- (Modern Jewish experience (Bloomington, Ind.), 2002)
Female, Jewish, and Educated presents a collective biography of Jewish women who attended universities in Germany or Austria before the Nazi era. To what extent could middle-class Jewish women in the early decades of the 20th century combine family and careers? What impact did anti-Semitism and gender discrimination have in shaping their personal and professional choices? Harriet Freidenreich analyzes the lives of 460 Central European Jewish university women, focusing on their family backgrounds, universi.